Management information systems - storage security - El Hallag, Ahmed Yousef (Univerzita Pardubice, 2008)
This bachelor work is a research based document. It elaborates briefly on management information systems, their establishment and implementation. It later focuses on their security measures using the support of IS/IT.
Management information systems - zabezpečení informací
Keywords: management information systems; information technologies; Information; storages; security; manažerské informační systémy; Informační technologie; Informace; úschovy; zabezpečení